Living Prayer: Its Contributions for the World’s Ecosystems and Interreligious Harmony - Diane Butler (Universitas Udayana, 2016)
Since the Assisi Declarations on man and nature were initially created by leaders from Buddhism, Christianity, Hinduism, Islam and Judaism at an interreligious meeting convened by World Wildlife Fund in Assisi, Italy in September 1986 and the first World Day of Prayer for Peace attended by representatives of many more faiths and ethnic religions in October 1986 in Assisi, a contemporary environmental movement that clearly encompasses spiritual as well as social dimensions has been growing exponentially. However, given the acceleration of global warming and environmental crises differentially affecting parts of the earth, we have now to ask, what is the application of the Assisi Declarations and peace prayers for facing the needs of today and in the future? This article thus aims to convey some ideas on the contributions of living prayer and associated creative practices in Indonesia in general, and Bali in particular, by discussing three dimensions: (a) the ways in which living prayer is embodied in customary ritual arts as well as in new forms of artistic expression; (b) its contributions to environmental, socio-cultural, and economic well-being; and (c) the means by which it fosters intercultural and interreligious dialogue and creativity. To illustrate this, I draw on examples of prayers and art from public participatory intercultural Sharing Art events held in Bali and Java as well as in other countries.